THE EFFECT OF BENSON RELAXATION TECHNIQUES ON PAIN SCALE IN POST OPERATION AT IMELDA PEKERJA INDONESIA HOSPITAL - Wellina Sebayang; Fitriana Ritonga; Devi Damayanti (Bina Sehat Press. Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2022)
Benson Relaxation is the development of a relaxation response method by involving the patient's belief factor. Relaxation using breathing techniques commonly used in hospitals in patients who are experiencing pain or experiencing anxiety. The purpose of this study was to determine the effect of Benson relaxation on pain intensity in postoperative patients at Imelda Pekerja Indonesian Hospital in Medan. This type of research is Quasy experimental design with one group pretest and posttest. The population in this study amounted to 30 postoperative patients at Imelda Pekerja Indonesian Hospital in Medan. The population of this study were all postoperative patients as many as 30 patients. Sampling technique used is Non Probity Sampling with Totally Sampling method. The data collection method used observation sheets before and after the Benson relaxation was given. The statistical test used in this study was the Wilcoxon Sign Rank Test with a 95% confidence level (α = 0.05) and a p value of 0.00 < 0.05. It can be concluded that there is a significant effect on the Benson relaxation technique on the pain scale in postoperative patients at the Imelda Pekerja Indonesian Hospital Medan in 2022